Effects of Starvation, Age, and Mating Status on Flight Capacity of Laboratory-Reared Brown Marmorated Stink Bug (Hemiptera: Pentatomidae). Issue 3 (2nd April 2021) - Aita, Rafael Carlesso; Kees, Aubree M; Aukema, Brian H; Hutchison, W D; Koch, Robert L
Abstract: The brown marmorated stink bug, Halyomorpha halys (Stål) (Hemiptera: Pentatomidae), is an invasive species to North America and has spread throughout most of the territory. Understanding flight in H. halys is crucial to understanding the dispersal capacity and developing forecasting models for this pest. The purpose of this research was to assess the effects of starvation, age, mating status, sex, and preflight weight on flight parameters of laboratory-reared H. halys using computer-monitored flight mills. The mean flight distance observed over a 24-h period was 266 m and the maximum distance was 7.3 km. Overall, the flight capacity of males and females was similar, even though females weighed more than males. The proportion of H. halys that initiated flight was not affected by starvation, age, or mating status. The number of bouts of individual flights and velocity significantly increased with longer durations of starvation. The number of bouts significantly decreased with increasing age. The total distance flew and total flight time was not affected by starvation, age, or mating status. Although some statistical differences were seen across the experiments, these differences likely represent minimal ecological significance. Therefore, these results suggest that H. halys are remarkably resilient, which may contribute to their success as an invasive species. The findings of this study could help better predict the dispersal potential of H. halys in Minnesota.